The incidence of adjacent segment disease requiring surgery after anterior cervical diskectomy and fusion: estimation using an 11-year comprehensive nationwide database in Taiwan - Wu, Jau-Ching; Chen, Yu-Chun (Neurosurgery, 2012)
AbstractBackground:. The incidence of symptomatic adjacent segment disease (ASD) after anterior cervical diskectomy and fusion (ACDF) was reported as 2.9%/y in
Gesehen am 15.10.2018